European Actors and Disinformation: the dispute between fact-checking, alternative agendas and geopolitics - Tuñón Navarro, Jorge (2019)
The Brexit referendum is a good example of the particular vulnerability of the European project when fighting disinformation. Therefore, EU institutions have developed a series of initiatives throughout 2018 to define a European strategy to counter disinformation that emphasizes the responsibility of social networks in reporting false content. In addition, given the weakness of the European public sphere, the European institutions support the creation of European networks of fact checkers. This strategy implies the denunciation of lies, rather than the promotion of alternative interpretive frames, which authors like Lakoff (2004) consider an error from a framing point of view. Empirically, we demonstrate through an analysis of the main networks of actors on this matter (academics, foundations, think tanks, media, social network platforms and fact checkers) that there is a dispute to define the best way to combat disinformation at the European level.